2011
DOI: 10.1007/s11771-011-0838-8
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic drag analysis of double-deck container vehicles with different structures

Abstract: To study the aerodynamic performance of a new six-axis X2K double-deck container vehicle, numerical simulation was done based on three-dimensional, steady Navier-Stokes equations and k−ε turbulence model. The results show that the pressure on the front surface of vehicle is positive, and others are negative. The maximum negative one appears as a "gate" shape on front surfaces. The pressure on vehicle increases with train speed, and pressure on vehicles with cross-loaded structure is smaller than that without i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Following the work, the air is assumed to be viscous and incompressible, according to Anderson (2010). Owing to the benefit of reducing computing consumption, good stability for the solution and more accurate mimicking of the flow physics near the wall boundaries (Xie et al , 2014; Chitrakar et al , 2017; Kummitha et al , 2021), the standard k - ɛ turbulence model with enhanced wall treatment is adequate for modeling large-scale flow near trains or other complex structures under crosswind conditions (Li et al , 2011b; Liu and Zhang, 2013; Zhang et al , 2017). Furthermore, according to the previous investigations, a high agreement is shown between the measured data and the numerical results, when the standard k - ɛ model is used for simulating the turbulence transport under the wind-driven rain environment (Kubilay et al , 2013; Pettersson et al , 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Following the work, the air is assumed to be viscous and incompressible, according to Anderson (2010). Owing to the benefit of reducing computing consumption, good stability for the solution and more accurate mimicking of the flow physics near the wall boundaries (Xie et al , 2014; Chitrakar et al , 2017; Kummitha et al , 2021), the standard k - ɛ turbulence model with enhanced wall treatment is adequate for modeling large-scale flow near trains or other complex structures under crosswind conditions (Li et al , 2011b; Liu and Zhang, 2013; Zhang et al , 2017). Furthermore, according to the previous investigations, a high agreement is shown between the measured data and the numerical results, when the standard k - ɛ model is used for simulating the turbulence transport under the wind-driven rain environment (Kubilay et al , 2013; Pettersson et al , 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Z. armatum 'YT-03' had lower symmetry and was more evolved. Some plant karyotypes can evolve from diploid to polyploid [49]. The evaluation of the five materials showed that the karyotype of varieties and cultivars of Z. armatum also potentially evolved from diploid to polyploid.…”
Section: Divergence Stages Of Five Z Armatum Materialsmentioning
confidence: 99%
“…Thus, a number of studies on freight train aerodynamics have been performed in the last decade. The numerical work of Li et al 4 and the experimental work of Watkins et al 5 has shown that there is a significant effect of the inter-car gaps on the aerodynamic performance of freight trains. They demonstrated that reducing the size of the inter-car gaps by placing smaller containers in-between existing containers can result in an up to 50% reduction in drag force.…”
Section: Introductionmentioning
confidence: 99%